1977
DOI: 10.1039/f19777301393
|View full text |Cite
|
Sign up to set email alerts
|

Electron spectroscopic study of nitrogen species adsorbed on copper

Abstract: The interaction of a number of nitrogen containing molecules (NO, NH3 and N2H4) with copper has been investigated by electron spectroscopy. Nitric oxide is shown to be molecularly adsorbed in a linearly bonded configuration at 85 K ; this adlayer is unstable above 120 K, resulting in an exclusively oxygen adlayer at 295 K, the nitrogen being desorbed. At 85 K N(1s) peaks observed at 401 and 406 eV are associated with NOs-(ads) and NOd+(ads) species, the former dissociating and the latter desorbing on thermal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…The plot also shows an estimate of the sticking probability for the two major processes at these temperatures, corresponding to (a) all products formed via (NO)2 formation and (b) Nad + Oad. NO g + *nn + NO ad f (NO) 2ad (2′′) NO p f N ad + O ad (6) particular, the NO ad monomer is more stable on Cu than on Ag, although the dimer is observed at higher coverages. Secondly, complete scission of both O-N bonds in the dimer occurs in two steps on Cu to yield gaseous N 2 at low temperatures, but not on Ag where only one O-N bond is broken.…”
Section: Exposure Range 03-06 L (Stage Ii)mentioning
confidence: 90%
“…The plot also shows an estimate of the sticking probability for the two major processes at these temperatures, corresponding to (a) all products formed via (NO)2 formation and (b) Nad + Oad. NO g + *nn + NO ad f (NO) 2ad (2′′) NO p f N ad + O ad (6) particular, the NO ad monomer is more stable on Cu than on Ag, although the dimer is observed at higher coverages. Secondly, complete scission of both O-N bonds in the dimer occurs in two steps on Cu to yield gaseous N 2 at low temperatures, but not on Ag where only one O-N bond is broken.…”
Section: Exposure Range 03-06 L (Stage Ii)mentioning
confidence: 90%
“…Although the experimental works reported that not NO dissociative adsorption but NO dimerization occurred on Cu and Ag surfaces, [5][6][7][8][9][10][11] the computational results with Ag 2 and Cu 2 indicated that the NO dimerization on these metal clusters was endothermic, that is, NO dimer was not formed on Ag 2 and Cu 2 , suggesting that these clusters are far from real cluster and surface. As the first step of size effect investigation, we employed Ag 5 and Cu 5 .…”
Section: Comparison Of No Dimerization Between M 2 and Mmentioning
confidence: 99%
“…[5,6] NO dimer was also experimentally observed on Cu(100) and Cu(111) surfaces. [7][8][9][10][11] In the case of NO dimer adsorption, formation of N 2 O species has been often observed. [5][6][7][8][9][10][11] Because N 2 O is one kind of reduced species of NO molecule, NO dimer adsorption is expected to be useful for NO reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption of NO molecules on Cu surfaces has also been studied extensively [22], because of the practical interest in the development of catalysts that transform the NO x species into nonpolutant products. It is known from electron spectroscopy and electron diffraction that the NO molecule adsorbed on a Cu surface dissociates at temperatures as low as 80 K [23][24][25]. The mechanism of this dissociative chemisorption has been partially discussed [15]; however, it is also important to investigate the electronic structure of the adsorbate experimentally for the model clusters of the NO adsorbed on a Cu surface, Cu n -NO.…”
Section: Introductionmentioning
confidence: 98%